The clinical use of the MOGE(S) classification in the differential diagnosis between idiopathic hypertrophic cardiomyopathy and its phenocopies - A. Poliakova; A. Krutikov; E. Semernin; A. Kostareva; A. Gudkova (Российский кардиологический журнал, 2019)
Aim. To determine  the relation between  idiopathic hypertrophic  cardiomyopathy (HCM) and HCM phenocopies, as well as to study the etiological pattern  of HCM phenocopies in patients  of the  North-Western  region  of Russia  in different age groups.Material  and  methods. The  study  included  321  patients  with left  ventricular hypertrophy ≥15 mm according  to an echocardiography. All the necessary clinical, laboratory and instrumental  diagnostic  methods  for verification of HCM and HCM phenocopies was carried out. In the diagnosis, the MOGE(S) classification was used.Results.  At  a  young  age,   idiopathic  HCM accounts  for  92%  (n=62),  HCM phenocopies — 8% (Danon disease (n=1 (2%)), isolated cardiac  sarcoidosis (n=1 (2%)) and systemic AL amyloidosis (n=3(4%)). Idiopathic HCM is also found in the vast majority of middle-aged patients — in 85% of cases (n=86). HCM phenocopies (15%) were in isolated  cardiac  sarcoidosis (n=3 (3%)), systemic amyloidosis variants (n=12 (12%)) — AL amyloidosis with predominant cardiac injury (n=11,11%), hereditary transthyretin amyloidosis (n=1,1%). Of the 153 examined  patients  with HCM aged  ≥60 years  old, 85% (n=131) were diagnosed with idiopathic HCM. HCM phenocopies were detected in 15% of cases (n=22). In the etiological pattern  of HCM phenocopies, transthyretin  amyloidosis was  10%:  non-hereditary   transthyretin  amyloidosis  — 6%  (n  =  9),  hereditary transthyretin  amyloidosis — 4% (n=6); AL amyloidosis — 4% (n=6). In 1 patient, acromegalic  cardiomyopathy (1%) was verified. In this article, we present 3 clinical cases that demonstrate the difficulty of differential diagnosis  between  idiopathic HCM and various HCM phenocopies.Conclusion. In all age groups,  idiopathic HCM predominates. Lysosomal storage diseases classify as  rare  diseases. Isolated  cardiac  injury with amyloidosis  and sarcoidosis is widely met but less often diagnosed. We determined a high frequency of isolated cardiac injury with amyloidosis under the age of 45 years. The etiological pattern  of HCM phenocopies in the elderly is represented mainly by transthyretin cardiomyopathic  amyloidosis of hereditary and non-hereditary  variants.